Chemical Language Modeling: A Comparative Approach to SMILES and SELFIES Tokenization - Mayuare, Miguelangel Leon (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science